European Trends in Local Public Administration: Adapting to Globalization - Florentina CRETU, Raluca; DOBRE, Florin; MONCEA, Madalina; Octavian MANESCU, Catalin (European Journal of Sustainable Development, 2024)
The trend of globalization, accompanied by the dynamic development of social systems, places national states in a completely new position, in which institutions and administrative systems must be adapted. Any intervention in the field of public administration reform implies changes in major components, including central administration, local administration and public services. On the other hand, the development of democracy calls for the establishment of a new relationship between citizens and the administration, increasing and strengthening the role of local authorities and reconsidering the partnership with civil society. There are numerous reasons for the structural and functional modernization of the public administration in Romania, starting from the need for more efficient functioning of government institutions to the aspiration to become a member of the European Union. The present study aims to address these aspects, taking into account the impact of the reform measures at the public administration level that have been undertaken recently. Through the coherent and continuous development of the decentralization process in the next period, we will be able to witness the increase in the quality and efficiency of public services, and local administrations will respond to the demands of citizens and local development in an improved way. Keywords: development, Europe, municipalities, public administration